Real-time monitoring system of electricity consumption in office space operation / Siti Sabariah Norazan - Norazan, Siti Sabariah (2019)
Electricity is an ever-essential issue catching the attention of all developed countries in the world. Individuals on the planet has been subjected to power and overrun all parts of human lives. Despite the ongoing advances in technology, there was augmentation in energy demand in these previous years which trade off the few responsibilities to lessen ozone depleting substance emanations to the environment since the electrical energy generation is still profoundly dependent on the utilization of non-renewable energy sources. With real-time monitoring system, the expense per kWh varies with time as an outcome of the changing supply and demand in the market based on the energy consumption by the consumers. The system would have the capacity to decrease the electricity cost by knowing the load consumptions for their day by day energy consumptions. The Internet of things (IoT) is getting more attention in these ongoing years. Allows gadgets connected to the web to be observed and controlled by remote users. Nonetheless, users need to know the vital utilization of IoT for instance providing energy efficiency and energy monitoring. The purpose is to give better understanding on their electricity usage patterns. Henceforth expedites them to the mindfulness on the amount of electricity consumed by various appliances and equipment and improving their understanding on electric bills. To be more transparent and informative to users.